Title production and characterization of plastic from marine algae - Nadarajan, Ramanan (2013)
The two main objective of this research is to test the viability of using marine algae as a profound bio-filler for the production of plastic where the plastic produce will have the tendency to reduce usage of non-renewable recourse which contributes to severe ecological problems. The second objective is to characterize the plastic blend produced using marine algae via physical, mechanical and thermal testing. In this study, Marine algae and Low density polyethylene is used as raw material and blended to produce plastic sample which later on was characterized using Differential Scanning Calorimeter (DSC), Thermogravimetry Analyzer (TGA), and tensile tester as well as water absorption tests. The results concluded that these red marine algae are not suitable for plastic production without any modification. This is due to the fact that it have weak mechanical properties and also very high water absorbance level which contributes mechanical failure under moist conditions.